2021
DOI: 10.5005/jp-journals-10071-23870
|View full text |Cite
|
Sign up to set email alerts
|

Role of Invasive Mechanical Ventilation and ECMO in the Management of COVID-19: A Systematic Review

Abstract: A bstract Objectives This systematic review aims to provide insight into the outcome of extracorporeal membrane oxygenation (ECMO) and invasive mechanical ventilation use in critically ill COVID-19 patients. Data sources Electronic databases PubMed Central and PubMed were searched from January 2020 to June 2020 for published studies about ECMO and/or invasive mechanical ventilation use in COVID-19 patients. Data Extraction and Study Selection:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
(93 reference statements)
0
4
0
Order By: Relevance
“…Another recent study shows a 40% mortality in COVID 19 and ECMO patients. Age, multiple comorbidities, lower pre-ECMO pH, renal replacement techniques, requirement of vasoactive drugs and bleeding were predictors of death in these patients [68][69][70][71].…”
Section: Are Drug Association Studies Relevant and Necessary In Diffe...mentioning
confidence: 90%
“…Another recent study shows a 40% mortality in COVID 19 and ECMO patients. Age, multiple comorbidities, lower pre-ECMO pH, renal replacement techniques, requirement of vasoactive drugs and bleeding were predictors of death in these patients [68][69][70][71].…”
Section: Are Drug Association Studies Relevant and Necessary In Diffe...mentioning
confidence: 90%
“… 97 The utility of ECMO should be evaluated based on current circumstances, considering the need for specialized patient care and the capacity to manage a high volume of patients through centralization. 98 …”
Section: Extracorporeal Membrane Oxygenation and Coronavirus Disease ...mentioning
confidence: 99%
“…From a dental perspective, the outbreak of the COVID-19 pandemic poses a threat to the practice of dentistry. This is because the oral cavity should be considered a preferential route for the entry or transmission of the related-virus (SARS-CoV-2) among populations that can occur directly or indirectly [1-3], particularly in nosocomial environments at risk [4]. Recent studies have shown that COVID-19 infection and severity can be linked to the presence of periodontitis [5].…”
Section: Introductionmentioning
confidence: 99%
“…particularly in nosocomial environments at risk [4]. Recent studies have shown that COVID-19 infection and severity can be linked to the presence of periodontitis [5].…”
Section: Introductionmentioning
confidence: 99%